Business Management Development Model For “Cireng Ceu Iin” Enterprises In Padasuka Village, Baros District, Serang Regency - Khaeruman; M. Ilmi Syiraf; Defi Mugfiroh; Yeny Safriyana; Fariha Maulani; Difa Ramadani Nurhidayati (International Journal Of Community Service, 2021)
Marketing is a business function that identifies current unmet wants and needs and manages their size, determines which target markets the organization can best serve, and determines the appropriate range of products, services and programs to serve those markets. So marketing acts as a liaison between the needs of the community and the pattern of industrial responses.This community service activity is carried out at the home of the business actor who has the address. The method used in the implementation of community service activities is business assistance.The purpose of this method is the participatory-lecture method,discussion-information and continued with direct training on making business management development models for business actors "Cireng Ceu Iin" in Padasuka Village, Baros District, Serang Regency.In a business, it is better to plan carefully both in terms of future prospects and the management system that can be done to manage the business in question. In addition, it is necessary to take into account the prospect of competition, market segmentation and the smooth running of its business. Especially for the management of the Cireng-making business, it is necessary to pay attention to the availability of raw materials in the form of sago and flour which must be processed into dough. Setting the selling price is one of the factors that must be considered in a business. Prices must be realistic but do not forget the capital spent to carry out the business in question.